miR-141 Promotes Colon Cancer Cell Proliferation by Targeted PHLPP2 Expression Inhibitionn - Fang F (Cancer Management and Research, 2020)
Fazhuang Fang,1 Ling Cheng,2 Xiaotang Wu,2 Minfeng Ye,3 Huizhong Zhang1 1Department of Hepatobiliary, Pancreatic and Gastric Surgery, Jinhua Guangfu Hospital, Jinhua 321000, People’s Republic of China; 2Shanghai Engineering Research Center of Pharmaceutical Translation, Shanghai, People’s Republic of China; 3Department of Gastroenterology, Shaoxing People’s Hospital, Shaoxing, People’s Republic of ChinaCorrespondence: Huizhong ZhangDepartment of Hepatobiliary, Pancreatic and Gastric Surgery, Jinhua Guangfu Hospital, No. 1296 North Ring Road, Jinhua 321000, People’s Republic of ChinaTel +86 13735796710Email zHANGHUIZHONG2@163.comObjective: Colon cancer (CC) is the third most common cancer with a high rate of incidence and mortality. Therefore, it is highly necessary to explore novel targets of CC.Methods: The miRNA-seq and RNA-seq data of CC were accessed from the TCGA database. Differential analysis was performed using the “edgeR” package to identify differentially expressed miRNAs (DE_miRNAs). The downstream target genes of the target miRNA were then predicted by miRNA target prediction databases to identify the target mRNA. Normal colon cell line CCD-18Co and CC cell lines HCT-116, HT-29, SW620 and SW480 were chosen, and qRT-PCR was conducted to detect miR-141 expression in these cell lines. qRT-PCR and Western blot were carried out to determine PHLPP2 mRNA and protein expression, respectively. Dual-luciferase reporter gene assay was performed to verify the targeting relationship between miR-141 and PHLPP2 3ʹUTR. CCK-8 assay and colony formation assay were carried out to detect cell proliferation. Meanwhile, tumor xenograft model in nude mice was constructed to assess CC cell tumorigenic ability in vivo.Results: miR-141 was markedly up-regulated in CC tissue. CC cell proliferation and in vivo tumorigenic ability were suppressed by miR-141 silencing but promoted by miR-141 over-expression. PHLPP2 was significantly down-regulated in cancer tissue. Dual-luciferase reporter gene assay indicated that miR-141 could bind to PHLPP2 3ʹUTR. PHLPP2 expression was noticeably elevated upon miR-141 deficiency but significantly inhibited upon miR-141 over-expression. CCK-8 and colony formation assay suggested that miR-141 facilitated CC cell proliferation by silencing PHLPP2.Conclusion: miR-141 promotes CC cell proliferation by targeted silencing PHLPP2.Keywords: miR-141, PHLPP2, colon cancer, proliferation